2020
DOI: 10.37723/jumdc.v11i1.262
|View full text |Cite
|
Sign up to set email alerts
|

The PROBLEMATIC INTERNET USE AMONG HEALTHCARE PROFESSIONALS: EMERGING BEHAVIORAL PATTERNS IN SOCIAL NETWORKING SITES ADDICTION

Abstract: ABSTRACT: BACKGROUND & OBJECTIVE: Internet has swayed all aspects of human society and the exponential rise in global internet users indicates that internet & Social Networking sites (SNS) have become an essential part of the daily lives of people with potentially addictive effects of its overuse. This may lead to social isolation, depression & professional effects. This behavioral addictive pattern has also been observed in increasing trend among healthcare professionals worldwide. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…All selected studies were cross-sectional. Three studies ( n = 770) reported internet addiction in medical residents only (Grover et al, 2019; Mobasher et al, 2015; Schmidt et al, 2019), one in faculty members only ( n = 69) (Grover et al, 2019), one in nurses only ( n = 564) (Lin et al, 2013), while three studies reported internet addiction in mixed cohort of medical professionals that included residents, faculty members, nurses and or administrative workers ( n = 415) (Avcı & Şahin, 2017; Prakash, 2017; Sohail et al, 2020). Sample sizes across studies ranged from 69 faculty members (Grover et al, 2019) to 564 nurses (Lin et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All selected studies were cross-sectional. Three studies ( n = 770) reported internet addiction in medical residents only (Grover et al, 2019; Mobasher et al, 2015; Schmidt et al, 2019), one in faculty members only ( n = 69) (Grover et al, 2019), one in nurses only ( n = 564) (Lin et al, 2013), while three studies reported internet addiction in mixed cohort of medical professionals that included residents, faculty members, nurses and or administrative workers ( n = 415) (Avcı & Şahin, 2017; Prakash, 2017; Sohail et al, 2020). Sample sizes across studies ranged from 69 faculty members (Grover et al, 2019) to 564 nurses (Lin et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In the total sample of healthcare workers, the meta-regression analysis showed that instrument used for assessment of internet addiction and healthcare job (resident vs nurse vs physician) (p values >.8) were not significant moderators of heterogeneity. Heterogeneity of internet addiction prevalence as a function of study country (Q = 16.172, p = .006) can be explained by high reported prevalence of internet addiction by one study from Pakistan (Sohail et al, 2020). Gender proportion, participant age and IA severity were not included in the meta-regression analyses because these variables were reported only by a small proportion of the identified studies.…”
Section: Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The study also showed that the healthcare job (resident vs nurse vs physician) was not associated with internet addiction. It is worth noting that only a few studies evaluated internet addiction in healthcare workers [20][21][22].…”
Section: Discussionmentioning
confidence: 99%